Etiology and management of damping-off of solanaceous vegetables - Bindu Menon (Department of Plant Pathology, College of Horticulture, 1996)
The etiology and management studies of damping-off of chilli, brinjal and tomato were carried out at the College of Horticulture, Vellanikkara, Thrissur during 1994-95. Bacterial wilt resistant varieties like Ujwala of chilli, Surya of brinjal and Sakthi of tomato were used for the study. Fungi like Aspergillus niger, A. flavus, Penicillium sp. And Rhizopus stolonifer were found associated with the seeds of chilli, brinjal and tomato. In addition, Curvularia lunata, Drechstera rostrata and Alternaria sp. were isolated from chilli, brinjal and tomato respectively. The pathogens responsible for pre and post-emergence-off were Rhizoctonia solani in summer and Pythium aphanidermatum, Phytophthora parasitica and Drechslera rostrata in rainy season. In varietal reaction, none of the varieties/genotypes was found to be immune to the disease. However, certain genotypes like LCA-304 of chilli, BB-60-C of brinjal and LE-79-5 of tomato showed resistance in both seasons. In in vitro studies, Bordeaux mixture (1%) and copper oxychloride (0.3%) completely inhibited the growth of P. aphanidermatum and P. parasitica whereas all six fungicides tested were found equally effective against R. solani and D. rostrata. in vitro evalution of Trichoderma viride, against all the isolated organisms of damping-off resulted in die-back and disintegration of the pathogens. Among the fungicides, seed treatment with chlorothalonil and thiram @ 2 g/kg seed gave maximum germination and minimum incidence of emergence damping-off both seasons. Bordeaux mixture (1%) and potassium phosphate (0.3%) have affected the germination of seeds especially in tomato. In rainy season, compared to all other treatments, maximum germination, and minimum pre-emergence damping-off was observed in solarized plots. Carbendazim (0.1%) and Bordeaux mixture (1%) treatments were found to be most effective in controlling post-emergence damping-off during summer and rainy season respectively. Solarization followed by application of antagonist was also equally effective as Bordeaux mixture treatment in rainy season.